El proceso de indización en la “unidad de documentación y archivo de la Procuraduría General del Estado”, delegación Quito, y su incidencia en la satisfacción de las necesidades informativas del usuario, durante el periodo 2012 - Saltos Sánchez, Gloria Haydee (2014)
This thesis called INDEXING PROCESS IN THE "UNIT DOCUMENTATION AND FILING OF THE ATTORNEY GENERAL OF THE STATE", QUITO DELEGATION AND ITS IMPACT ON THE SATISFACTION OF USER INFORMATION NEEDS. PERIOD 2012 is structured and developed in accordance with prevailing regulations of the National University of Loja. The overall objective was: To show the importance of indexing the records for timely satisfaction of user needs. The methods that were used were: Scientist, Analytical - Synthetic, Inductive- Deductive, and Statistical Model, the same that were used to describe and explain the form and the relationship between the Indexing Process Documentation and Archives Unit the Attorney General and the satisfaction of the Information Needs of Users. As research techniques were applied two surveys: workers of the Documentation and Archives, for to establish issues surrounding the indexing process, and to the users who come to the unit, to determine the level Needs Satisfaction Informative. Personnel serving in the Documentation and Archives Attorney General, 70% believe that through the process of indexing, the documents are organized logically, for posterior location, in an easy and timely and, 30%, indicates that the indexing process has nothing to do with the organization of documents. On the other hand, according to the results of the survey applied Users attending the unit, 70% stated that the indexing process facilitates timely access to the documents you need to meet your information needs, and, 30% think they do require Indexing Process to access the documents you want to see. Scenario that proves that there is a close relationship between the indexing process and meeting the information needs of users.